iFarm: Development of Iot-based system for Agriculture - Agarwal, Shrey; R. Jebakumar (International Journal of Psychosocial Rehabilitation, 2020)
Quality agriculture is aimed at elevating the management of farming and it requires the data of the work of agriculture. Farmers traditionally write data on a piece of paper but it is problematic along with tiresome to examine the agricultural statistics of the past and then supervise the amount of products of agriculture. The whole system contains IOT device, Web browsers and a cloud server. The IOT sensor will be placed in the farm. The hardware part will be the IOT sensor and the software part would be the cloud server and the database. These IOT devices will automatically transfer the data over the web server.